Efektivitas Pembelajaran Daring Di Sekolah MTSN 1 Murung - Nadia Nor Eka Wulandari; Dehen Erang; Windy Utami Putri; Nonsihai Nonsihai; Susi Sukarningsi; Rinto Alexandro; Hendrowanto Nibel; Susan Daniel (FKIP, Universitas Palangka Raya, 2022)
The purpose of this study is to find out the effectiveness of online learning in MTsN 1 Murung. The questions you want to answer through this study are: 1) To find out the effectiveness of online learning in MTsN 1 Moody. 2) To find out the advantages and disadvantages in the implementation of online learning in MTsN 1 Murung. 3) To know what needs to be improved so that the implementation of online learning runs better and in accordance with the wishes. This research uses qualitative research methods with qualitative descriptive analysis techniques or interview data collection and documentation. The subjects of the study were the head of the madrassa, teachers and learners of MTsN 1 Murung. The data analysis technique in this study uses qualitative descriptive data analysis of interactive models from Milles and Michael Huberman consisting of three concurrent activity paths, namely; data reduction, presentation of data, and withdrawal of conclusions. Based on the results of research and interviews showed that online learning in MTsN 1 Murung is not effective considering that in its short implementation so that gutu can not know whether learners have understood the material or not, the advantages of online learning in MTsN 1 Murung Raya that learning can be accessed anywhere and anytime, learners can learn independently, the provision of tasks is more structured through applications. While the lack of online learning in MTsN 1 Murung is monitoring or monitoring the situation of students sulik done, signals / connections that are less stable in some areas. The field that needs to be improved so that online learning can run well is to increase the creativity of teachers in making learning media that are easy to understand, monitoring / supervision to learners is more tightened, and cooperation between parents and teachers must be well established